Effect of muscle contraction in high-speed car-pedestrian impact: simulations for walking posture. (19th May 2011) - Soni, Anurag; Chawla, Anoop; Mukherjee, Sudipto; Malhotra, Rajesh
The effect of muscle contraction on lower extremity injuries for pedestrian walking posture in car-pedestrian lateral impact at 40 km/h is studied through FE simulations using the PMALE in the walking posture and front structures of a car. Impact on right (trailing) and left (leading) leg have been simulated as a cadaver and an unaware pedestrian with stretch based reflexes. It is concluded that with muscle contraction, risk of ligament failure decreases in lateral impacts and ligaments are differentially loaded due to impact at the two stance phases. Active muscles may not affect bone fracture in high speed car-pedestrian crashes.